DEVELOPING ENGLISH LEARNING MODULE IN STATE ELEMENTARY SCHOOL 056005 LANGKAT REGENCY - Friscilla Sembiring; Elisabeth Ruthana Lasmaria Sinaga (Universitas Negeri Medan, 2019)
Abstract : Developing English Learning Module in State Elementary School 056005 Langkat Regency. The purpose of this research is to develop learning modules for sudents grade V. This research is categorized into the type of research development (research and devolepment) by using Borg and Gall teaching material development model. Development research is oriented towards product development where the development process is described as thoroughly as possible and the product is finally evaluated. This research was conducted at SDN 056005Gohor Lama Grade V. Subjects in this study are the students of grade V of SDN 056005 Gohor Lama (Experiment) amounted to 20 students and garde V of SDN 050701 Hinai amounted 25 students (Comparator). The results of this study are developed teaching materials have met the Valid criteria. It can be seen from the results of validation of teaching materials conducted by the three validators declared social science materials of social skills based developed by researchers quite well, this is based on the assessment of the three validators for the design aspect the average the Mater aspect in stage I the average score is 60% and proceed to stage II the average score is 80%, and the last for the language aspect in phase I the average score is 40% then proceed to stage II with the average score is 84%. Teaching materials developed have met the practical criteria seen from teacher questionnaire results which reached 92% percentage. The use of learning materials based on social skills can improve student learning outcomes, the results obtained if you see the results of pre-test and postes where the class Experiment completeness of students reached 45% then at posttest increased to 70%. The result of pretest in comparison class student reach 54% then at the time of postes mask student reach 80%. Keywords : English Learning Module, , Elementary School Abstrak : Pengembangan Modul Pembelajaran Bahasa Inggris di Sekolah Dasar Kabupaten Langkat tahun ajaran 2019/2020. Tujuan dari penelitian ini adalah untuk mengembangkan modul pembelajaran untuk siswa kelas V. Penelitian ini dikategorikan ke dalam jenis pengembangan penelitian (penelitian dan pengembangan) dengan menggunakan model pengembangan bahan ajar Borg and Gall. Penelitian pengembangan berorientasi pada pengembangan produk di mana proses pengembangan digambarkan selengkap mungkin dan produk akhirnya dievaluasi. Penelitian ini dilakukan di SDN 056005 Old Gohor Kelas V. Subjek dalam penelitian ini adalah siswa kelas V SDN 056005 Old Gohor (Eksperimen) berjumlah 20 siswa dan garde V SDN 050701 Hinai berjumlah 25 siswa (Pembanding). Hasil penelitian ini adalah bahan ajar yang dikembangkan yang telah memenuhi kriteria Valid. Hal ini dapat dilihat dari hasil validasi bahan ajar yang dilakukan oleh ketiga validator yang mendeklarasikan materi ilmu sosial berdasarkan keterampilan sosial yang dikembangkan oleh peneliti dengan cukup baik, hal ini didasarkan pada penilaian ketiga validator untuk aspek desain rata-rata aspek Mater pada tahap I skor rata-rata adalah 60% dan melanjutkan ke tahap II skor rata-rata adalah 80%, dan yang terakhir untuk aspek bahasa pada fase I skor rata-rata adalah 40% kemudian melanjutkan ke tahap II dengan skor rata-rata adalah 84%. Bahan ajar yang dikembangkan telah memenuhi kriteria praktis dilihat dari hasil angket guru yang mencapai persentase 92%. Penggunaan materi pembelajaran berdasarkan keterampilan sosial dapat meningkatkan hasil belajar siswa, hasilnya diperoleh jika Anda melihat hasil pre-test dan posttest dimana kelas Eksperimen siswa mencapai 45% kemudian pada posttest meningkat menjadi 70%. Hasil pretest pada siswa kelas perbandingan mencapai 54% kemudian pada saat posttest siswa topeng mencapai 80%.Kata Kunci : Modul Pembelajaran Bahasa Inggris, Sekolah Dasar